Elbow Arthroscopy - Pederzini, Luigi Adriano; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book stems from the decision by the Education Committee of The International Society of Arthroscopy, Knee Surgery and Orthopaedic Sports Medicine (ISAKOS) to charge the editors, Luigi Pederzini, Marc Safran, and Greg Bain, with the task of describing the basic techniques and the more advanced aspects of elbow arthroscopy with a view to encouraging surgeons to follow safe guidelines and to better understand procedures of varying difficulty. The authors are respected experts and pioneers in elbow arthroscopy and provide perspectives from North America, Australia, and Europe. They have in common the ability to teach complex procedures in a simple way.   This book will be invaluable in assisting the developing surgeon to perform elbow arthroscopic surgery to best effect. For the experienced surgeon, it will serve as an excellent reference and source of information on the latest developments. Finally, for the academic surgeon it poses stimulating challenges to advance elbow surgery into a new era.
Introduction -- Anatomy and portals -- Arthroscopic Technique -- OCD and loose bodies -- Elbow arthroscopy in stiff elbow -- Epicondilitis -- Comparison between open and arthroscopic technique in stiff elbow -- Elbow arthroscopy and instability -- Endoscopy around the elbow -- Elbow arthroscopy in elbow fracture -- Elbow arthroscopy complications -- Elbow arthroscopy in the future.
Keywords: Orthopedics; Sports medicine; Surgical Orthopedics; Sports Medicine